The zinc transporter ZIPT-7.1 regulates sperm activation in nematodes. - Yanmei Zhao; Chieh-Hsiang Tan; Amber Krauchunas; Andrea Scharf; Nicholas Dietrich; Kurt Warnhoff; Zhiheng Yuan; Marina Druzhinina; Sam Guoping Gu; Long Miao; Andrew Singson; Ronald E Ellis; et al. (PLoS Biology)
Sperm activation is a fascinating example of cell differentiation, in which immotile spermatids undergo a rapid and dramatic transition to become mature, motile sperm. Because the sperm nucleus is transcriptionally silent, this transition does not involve transcriptional changes. Although Caenorhabditis elegans is a leading model for studies of sperm activation, the mechanisms by which signaling pathways induce this transformation remain poorly characterized. Here we show that a conserved transmembrane zinc transporter, ZIPT-7.1, regulates the induction of sperm activation in Caenorhabditis nematodes. The zipt-7.1 mutant hermaphrodites cannot self-fertilize, and males reproduce poorly, because mutant spermatids are defective in responding to activating signals. The zipt-7.1 gene is expressed in the germ line and functions in germ cells to promote sperm activation. When expressed in mammalian cells, ZIPT-7.1 mediates zinc transport with high specificity and is predominantly located on internal membranes. Finally, genetic epistasis places zipt-7.1 at the end of the spe-8 sperm activation pathway, and ZIPT-7.1 binds SPE-4, a presenilin that regulates sperm activation. Based on these results, we propose a new model for sperm activation. In spermatids, inactive ZIPT-7.1 is localized to the membranous organelles, which contain higher levels of zinc than the cytoplasm. When sperm activation is triggered, ZIPT-7.1 activity increases, releasing zinc from internal stores. The resulting increase in cytoplasmic zinc promotes the phenotypic changes characteristic of activation. Thus, zinc signaling is a key step in the signal transduction process that mediates sperm activation, and we have identified a zinc transporter that is central to this activation process.